Wood hydrosystem of three cultivars of Vitis vinifera L. is modified in response to contrasting soils - Roig Puscama, Federico Ariel (2021)
Background and aims: In Vitis vinifera L., the same genotype can express different phenotypic characteristics depending on the environmental conditions, e.g. soil deepness. Wood anatomy, specifically xylem vessel traits, provide information about the plant’s eco-physiological responses to the environment. Slight changes in vessel diameter and density may impact plant hydrosystem functionality, since large vessels are more efficient in the volume of transported water compared to narrower ones, although the latter are more effective in avoiding stress-induced embolism. The aim of this study was to analyze variations in the wood hydraulic structure of three grapevine cultivars, induced by soils with strong contrast in depth, texture and rock volume, providing evidence of their adaptative capacities. Methods: Anatomical and growth traits of each annual growth ring were measured in 8-year-old plants of Bonarda, Malbec and Tempranillo cultivars growing in contrasting depths of soils. Results: Bonarda exhibited no differences in wood productivity between soils with different depths, showing the ability to modulate the earlywood vessel lumen area. Malbec and Tempranillo did show differences in wood productivity between the two types of soils, with major changes in the trade-off between vessel density and lumen area in Tempranillo, while in Malbec there were few changes in the vessel traits. Conclusions: Xylem hydraulic characteristics of the grapevine stems varied in response to soil environment and cultivar. This knowledge may help to select management strategies in areas of soil heterogeneity.